The use of digital games for teaching gross anatomy: an experience report (Research, Society and Development, 2020)
The modern Anatomy education allows the use of digital tools which innovate the way we study the human body. This paper aimed to report our experience and analyse how an anatomy website containing games was accessed in a gross anatomy discipline. The website was provided as an additional (non-mandatory) resource to the topics discussed in the lecture programme, in anatomy. On the website, the student could find several anatomical topics. This was an optional tool and students were not required to access the website nor play the games. The data collected by Google Analytics were tabulated, showing the page views according to the anatomy content and the daily number of page views. During the academic semester, the highest number of views corresponded to the subjects taught during the lectures. Besides, the “peak” of the views always occurred on the days before the assessment tests. It was concluded that games are attractive learning tools and students used them for the coursework in anatomy (especially on the day before assessments), even if this activity was not mandatory. This methodology can be an effective strategy in health blended education to motivate students as an extra-class study.